2018
DOI: 10.1097/ruq.0000000000000348
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Time for Developmental Dysplasia of the Hip Screening

Abstract: Late diagnosis of DDH might cause serious public health problems. On the other hand, early US examinations can result in false-positive diagnosis. Unfortunately, there is still confusion about the optimal time for DDH screening with US, especially among radiologists who are not specialized in DDH sonography. A US scan performed at eighth week of life can predict any pathology presence safely and correctly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
3
14
0
3
Order By: Relevance
“…This finding is in accordance with the only two other studies that were published regarding the timing of ultrasound screening for DDH [7,8]. Gokharman et al [7] compared the results of ultrasound screening at the fourth week of life to those at the 12th week of life, and found that ultrasound screening findings at the fourth week of life could successfully predict ultrasound findings at the 12th week of life. Similarly to our study, they found that ultrasound screening at the eighth week of life was more successful in predicting the results at the 12th week of life than ultrasound screening at the fourth week of life [7].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This finding is in accordance with the only two other studies that were published regarding the timing of ultrasound screening for DDH [7,8]. Gokharman et al [7] compared the results of ultrasound screening at the fourth week of life to those at the 12th week of life, and found that ultrasound screening findings at the fourth week of life could successfully predict ultrasound findings at the 12th week of life. Similarly to our study, they found that ultrasound screening at the eighth week of life was more successful in predicting the results at the 12th week of life than ultrasound screening at the fourth week of life [7].…”
Section: Discussionsupporting
confidence: 86%
“…However, the timing of ultrasound screening as part of the neonatal screening programme for DDH remains an ongoing topic of debate [6-9]. Ultrasound screenings that are performed too early can lead to a high incidence of false-positive or false-negative results, resulting in unnecessary anxiety, follow-up examinations, and financial burden [7,8]. In contrast, ultrasound screenings that are performed too late can result in delayed treatment, increasing the need for more invasive management, such as surgery, as well as imposing a financial burden [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study published recently, Gokharman et al has investigated the same question as our study using a different method and they found 8th week as the ideal time for screening which is a similar to the result of our study [18]. In total, 128 hips, 18% of all hips did not come for control.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have been conducted to identify the earliest possible time that ultrasound screening can be performed reliably for DDH. Gokharman et al [16] chose the fourth and eighth weeks of life as the timepoints for their study because of the observation from their clinical practice that most of ultrasound examinations performed during the first 4 -8 weeks of life. While, Lussier et al [11] chose the threshold of 28 days for their study because most screenings at their institutions were performed either in the first week of life or after 28 days of life.…”
Section: Ultrasound Screening For Ddhmentioning
confidence: 99%